The Effect of Various Legume Herbs Supplementation on Intake, Digestibility and Growth of Fat-tailed Lambs Given Mulato Grass - Marsetyo, Marsetyo; Mumu, Muhammad Ilyas; Basri, Muhamad (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2019)
This experiment was conducted to examine the effect of various legume herbs supplementation on feed intake, digestibility and liveweight gain of fat-tailed lambs given Mulato (Brachiaria mulato) grass. Twenty four male fat-tailed lambs (8 months of age and 12.73± 0.56 kg (SE) of initial liveweight) were randomly allotted to four treatment groups based on unfasted liveweight. Animals were housed in individual metabolism crates. The experiment was designed in a completely randomized block design, with four treatments and six replicates. The dietary treatment tested included Mulato grass ad libitum (M), M + Centrosema pascuorum (MCP), M + Dolichos lab lab (MDL) and M+ Clitoria ternatea (MCT). All supplement was offered at 1.5% body weight (W) per day. The experiment lasted for 10 weeks, with 2 and 8 weeks for adaptation and measurement period, respectively. The main parameter measured included feed intake, feed digestibility, and average daily liveweight gain (ADG). Results showed that total DM intakes (DMI) were not affected (P>0.05) by legume herbs supplementation. Total DMI was 2.75, 2.79, 2.84 and 2.87 %W/d for lamb treated with M MCP, MDL and MCT respectively. In contrast, supplementation with various legume herbs significantly increased (P <0.05) DM digestibility (DMD) and ADG of lamb received Mulato grass, with no significant difference (P>0.05) between legume herbs. Feed DMD was 58.17, 67.48, 64.91; 65.03% and ADG were 35.67; 58.39; 54.31 and 54.41 g/day, for lamb treated with M, MCP, MDL and MCT respectively. It was concluded that supplementation of legume herbs to fat-tailed lamb fed Mulato grass significantly increased DMD and ADG, but no significant differences across the legume herbs as feed supplements were observed.